Binding the past with digital: Film curation at Batu Api Library - Anwar, Rully Khairul; Khadijah, Ute Lies; Rodiah, Saleha (ProTVF, 2024)
Background: Digital curation is a growing concept that involves the selection, organization, and presentation of digital information for specific purposes. In this study, digital curation manages Batu Api Library’s film collection using digital technology. This trend is critical to keeping cultural information relevant and accessible to the public. Purpose: This study intends to examine the curation of digital films at the Batu Api Library and how users react to and value the library’s digital film curation results. Methods: This study is based on qualitative research. Batu Api Library conducted this study for three months. Interviews and questionnaires are research methods. Quantitative and qualitative data are collected in two phases. The types of data require different treatment methods. Thematic analysis provides qualitative data, while descriptive statistics uses quantitative data. The methodology provides a comprehensive understanding of the impact of technology on the curation of films and audience participation at Batu Api Library. Results: The study found overwhelmingly positive results for integrating digital technology into film curation at Batu Api Library. The experience engaged and educated many visitors and helped them understand historical and cultural differences. The youngest users were particularly engaged. Conclusion: The study found that digitizing film curation at Batu Api Library enhanced the visitor experience and historical insight. Responses, especially from younger participants, indicate that digital advances are beneficial. Implications: Digital film curation can enhance the museum experience and historical and cultural knowledge. Digital technology preserves and communicates cultural heritage in practical and theoretical ways.